Application of Cow Rumen Liquid in Palm Sugar Waste Compost for Cultivating Sweet Corn in Coastal Sandy Soil of Samas Beach Bantul - Larasati, Nadia Dwi; Budiyanto, Gunawan; Widyastuti, Titiek (Universitas Muhammadiyah Yogyakarta, 2017)
The research was conducted to study the effect of palm sugar waste compost using cow rumen activator on sweet corn cultivation and to determine the effective concentration of cow rumen activator and dose of sugar palm waste compost for sweet corn cultivation in coastal sandy soil of Samas Beach, Bantul. The research was arranged in Completely Randomized Design (CRD). A total of 11 treatments consisting of combination between the dose of sugar palm waste compost (tonnes/hectare) and various concentrations of cow rumen activators (%), with detail as follows: (1) 20 tonnes/hectare and 60%, (2) 20 tonnes/hectare and 70%, (3) 20 tonnes /hectare and 80%, (4) 20 tonnes/hectare and 90%, (5) 20 tonnes /hectare and 100%, (6) 25 tonnes/hectare and 60%, (7) 25 tonnes/hectare and 70%, (8) 25 tonnes/hectare and 80%, (9) 25 tonnes/hectare and 90%, (10) 25 tonnes/hectare and 100%, Â and (11) 20 tonnes/hectare of inorganic fertilizer. Each treatment was replicated four times. The results showed that the treatments of sugar palm waste compost with various concentrations of cow rumen activator and commercial compost had no significant effect on almost all plant parameters, except the root fresh weight. In addition, sugar palm waste compost with various concentration of cow rumen activator produced higher fresh weight of ear with husk compared to the potential yield of Sweet Boy variety. Dose of 20 tonnes/hectare of sugar palm waste compost with cow rumen activator at a concentration of 60% is the most effective treatment for sweet corn cultivation in coastal sandy soil of Samas Beach, Bantul.